PARENTS 2 study: consensus report for parental engagement in the perinatal mortality review process. (5th August 2019) - Bakhbakhi, D.; Siassakos, D.; Lynch, M.; Timlin, L.; Storey, C.; Heazell, A.; Burden, C.; ,
ABSTRACT: Objective: The PARENTS 1 study (Parents' Active Role and ENgagement in The review of their Stillbirth/perinatal death) found that parents would endorse the opportunity to give feedback into the perinatal mortality review (PNMR) process. In subsequent focus groups, healthcare professionals were positive about parental engagement, although they considered that there may be significant challenges. The objective of this study was to develop core principles and recommendations for parental engagement in PNMR in the UK. Methods: A two‐round Delphi technique was followed to reach consensus on core principles for parental engagement in the PNMR process; Round 1 included a national consensus workshop and Round 2 an online questionnaire. The consensus meeting was attended by a national panel of stakeholders (clinical and academic experts, parent advocates, managers and commissioners) in stillbirth and neonatal and bereavement care. To develop recommendations for parental engagement, participants discussed four key areas comprising: communication with parents, including receiving feedback; the format of the PNMR meeting; the parental engagement pathway; and challenging aspects of engaging with parents in reviews. Content analysis was conducted to generate recommendations from the meeting for a subsequent anonymous web‐based survey. Attendees of the consensus workshop and members of the PARENTS 2 Project Advisory Board were asked to rank recommendations using a 9‐point Likert scale from 1 (not important) to 9 (critically important). It had been agreed a priori, in compliance with established Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria, that 'consensus' would be achieved if over 70% of participants scored the principle as 'critical' (score of 7–9) and fewer than 15% scored the principle as 'not important' (score of 1–3). Principles for which consensus was achieved were included in the core recommendations. Results: Of the 29 invited stakeholders, 22 participated in the consensus meeting and 25 (86% response rate) in the subsequent online questionnaire in June 2017. Consensus was agreed on 12 core principles. Of the 25 participants, 96% agreed that a face‐to‐face explanation of the PNMR process was of critical importance, 72% considered that parents should be offered the opportunity to nominate a suitable advocate, 92% believed that responses to parents' comments should be formally documented, 96% indicated that it was vital for action plans to be translated into lessons learnt and that this process should be monitored, and 100% of stakeholders voted that a plain‐English summary should be produced for the parents following the meeting. There was good agreement on a further seven principles. Conclusions: Key national stakeholders were unanimously supportive of parental engagement in the PNMR process and agreed on core principles to make this process feasible, meaningful and robust. A 6‐month pilot of parental engagement in the PNMR process (PARENTS 2 study) in two UK units took place after the consensus on core principles. In collaboration with the National Perinatal Epidemiology Unit, the findings will inform the national standardized PNMR tool. © 2018 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.